ShielDroid: a hybrid ML and DL approach for real-time malware detection system in Android - Ahmed, Md Faisal; Biash, Zarin Tasnim; Shakil, Abu Raihan; Ryen, Ahmed Ann Noor; Hossain, Arman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.